2020
DOI: 10.1002/jctb.6332
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐electro‐Fenton systems for sustainable wastewater treatment: mechanisms, novel configurations, recent advances, LCA and challenges. An updated review

Abstract: Bio‐electro‐Fenton processes use biological electrons produced from bioelectrochemical systems to treat wastewater. The most significant advantages of bio‐electro‐Fenton systems are high effectiveness, low toxicity, gentle operation conditions, environmentally friendly treatment without sludge accumulation and energy conservation. Though promising, bio‐electro‐Fenton systems still face several challenges, such as high power density, H2O2 concentration, cathode materials, Fe2+ concentration and pH. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 160 publications
1
21
0
Order By: Relevance
“…This new approach to the treatment of resistant pollutants is attractive because it depends on producing free radicals, which are capable of oxidizing a wide range of pollutants to mostly harmless compounds, or complete mineralization to CO 2 , H 2 O and inorganic ions 11,12 . Electrochemical oxidation has been a promising technology for the degradation of micropollutants since the development of boron‐doped diamond (BDD) as anodic material 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This new approach to the treatment of resistant pollutants is attractive because it depends on producing free radicals, which are capable of oxidizing a wide range of pollutants to mostly harmless compounds, or complete mineralization to CO 2 , H 2 O and inorganic ions 11,12 . Electrochemical oxidation has been a promising technology for the degradation of micropollutants since the development of boron‐doped diamond (BDD) as anodic material 13 .…”
Section: Introductionmentioning
confidence: 99%
“…59,83 Generally, in the BEF system, in situ electrogenerated H 2 O 2 as a strong oxidant is the most important factor because H 2 O 2 is considered as a major source of cOH production in Fenton oxidation. 56 Therefore, this alternative approach, due to its high efficiency in the generation of Fenton reagent (e.g., H 2 O 2 ) and the saving costs related to the storage and transport of chemicals, is advantageous in comparison to the other AOP processes, such as conventional Fenton process, 84 UV/H 2 O 2 , 85 photocatalysis, 45,46 etc., in which H 2 O 2 needs to be added. 15 For example, Naushad et al 86 investigated the photo-degradation of methylene blue dye by applying different concentrations of H 2 O 2 .…”
Section: In Situ H 2 O 2 Concentration In the Bio-electro-fenton Systemmentioning
confidence: 99%
“…55 The results of previous studies showed that Shewanella, Geobacter, Arcobacter, Comamonas, Dechloromonas, Sphingobacterium, Desulfobulbaceae, Firmicutes, and Clostridium were wellknown and dominant electrochemically active bacterial species in mixed culture biolm that attach to the anodic electrode and form a dense biolm layer. 50,56,120…”
Section: Microbial Morphology Of the Anodementioning
confidence: 99%
See 1 more Smart Citation
“…Zero-valent iron is a strong reducing agent and has been used in particulate form for the removal of different organic (aromatic compounds) for groundwater remediation in the form of permeable reaction barriers [9] or as a slurry [10]. ZVI in the form of micropowders with diameters in the range of 50 to 200 µm [11] or in the form of nanopowders [12] shows a good reactivity in the presence of H 2 O 2 , meaning it could react with the surface iron to produce Fe 2+ and Fe 3+ and initiate the Fenton process [13][14][15]. Several studies have demonstrated that the optimal pH in the case of ZVI shifts to higher values (4 to 6), allowing outstanding degradation efficiencies for organic aromatic compounds [16,17].…”
Section: Introductionmentioning
confidence: 99%